From real to virtual: Kinematic adjustments in gait biomechanics of healthy older adults - Los Angeles, Emanuele; Cupertino, Layla; Pellegrino, Nathalia Mendes; de Souza, Brenda Luciano; Fukuchi, Claudiane Arakaki [UNESP]; Coelho, Daniel Boari (Elsevier, 2025)
Virtual reality (VR) technology has emerged as a valuable tool for gait rehabilitation, offering controlled and immersive environments that simulate real-world scenarios. Although little is known about how immersive VR affects gait biomechanics in older adults, we specifically investigate how walking in VR influences lower-limb kinematics compared to walking in a non-VR environment. Healthy older adults walked at their self-selected speed on an instrumented treadmill. VR participants experienced a fully immersive virtual industrial environment using the Computer Assisted Rehabilitation Environment (CAREN) system, while non-VR participants walked without a virtual environment. Kinematics were analyzed using one-dimensional Statistical Parametric Mapping to compare the VR and non-VR conditions across the gait cycle. Dimensionless gait speed was also assessed to ensure consistency in walking pace between groups. No significant differences were found between the VR and non-VR groups in dimensionless gait speed. However, phase-specific differences were observed in pelvic tilt, hip adduction/abduction, and ankle dorsiflexion/plantarflexion. These differences were small in magnitude (largest ≈4°) and within ranges often reported for measurement error or minimal detectable change in kinematics; therefore, they should be interpreted cautiously and as associations observed under differing acquisition/processing pipelines rather than as definitive effects attributable to VR. While overall speed was preserved, older adults made localized joint-level adjustments during specific gait phases, suggesting that immersive visual conditions interact with sensorimotor control.